Beyond Sensing, Seizing, and Reconfiguring: Toward Dynamic Capability Theory 4.0 through Agility and Adaptive Judgment Perspectives - A Systematic Literature Review - Aditya Halim Perdana Kusuma Putra; Misfah Muslimawati (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to examine the evolution of Dynamic Capability Theory by integrating organizational agility and adaptive judgment perspectives toward the development of Dynamic Capability Theory 4.0. Using a systematic literature review approach guided by the PRISMA framework, this study synthesizes prior research on dynamic capabilities, sensing, seizing, reconfiguring, organizational agility, managerial cognition, digital transformation, artificial intelligence, and organizational resilience. The findings indicate that the traditional sensing–seizing–reconfiguring framework remains theoretically relevant but requires extension to address contemporary organizational environments characterized by technological disruption, uncertainty, and rapid market change. Organizational agility emerges as both an antecedent and an outcome of dynamic capability development, enabling firms to respond quickly and flexibly to environmental turbulence. In addition, adaptive managerial judgment functions as a critical microfoundation that determines how organizations interpret information, make strategic decisions, and reconfigure resources effectively. Digital transformation and artificial intelligence further reshape the development of dynamic capabilities by strengthening data-driven sensing, strategic decision-making, innovation, and organizational resilience. This study contributes to strategic management literature by proposing an integrative perspective of Dynamic Capability Theory 4.0, which combines sensing, seizing, and reconfiguring with agility, adaptive judgment, digital intelligence, and resilience. The review provides theoretical implications for future research and practical insights for organizations seeking to sustain competitive advantage in complex and technology-mediated environments.